Caracterização e afinidades da ictiofauna do Reservatório de Juturnaíba, em Silva Jardim, Estado do Rio de Janeiro - Mendonça, Helaine da Silva (2004)
The fish fauna of the Juturnaíba Dam, in Silva Jardim, Rio de Janeiro State, Brazil, is characterized and its similarity with the faunas of the São João river basin, the extinct Juturnaíba Lake, and the rivers emptying into the present dam (Bacaxá, Capivarí and São João) is evaluated. The fish fauna of the dam and mouth of its contributors includes 44 species, of which only 22 occur in the reservoir itself. The original fish fauna of the extinct lake included 37 species. The dam formation has caused impact on the original lake fauna which, reduced, is today partially restricted to the lower course of the rivers emptying into the dam. The exotic Cichla monoculus, Clarias gariepinus and Oreochromis niloticus have been introduced and are established in the dam, what has been confirmed through the capture of individuals of several size classes. C ichla monoculus contributes to the degradation of the original fish fauna by predating on native species, with specimens of Platanichthys platana and Leporinus copelandii been found in the stomachs of young tucunarés. The loss of natural habitats of the original lake also contributed to the faunal impoverishment, since species dependent on the riparian vegetation for reproduction, shelter or feeding, such as Brycon insignis, Leporinus copelandii, Hoplerythrinus unitaeniatus and Cyphocarax gilbert, which were originally common in the lake, are today infrequent or rare in the dam.